เครียด กังวล เศร้า… เราจะรับมือกันอย่างไร? - ชุติมา สุรเศรษฐ (สาขาวิชาศึกษาศาสตร์ มหาวิทยาลัยสุโขทัยธรรมาธิราช, 2022)
State of problems and changing of environmental issues, assessed as uncontrollable threats to an individual, could cause many of us to feel stressed, anxious, and depressed. These issues can lead to the difficulties of living. Thus, accepting emotions that arise and learning to understand meaning, causes, attributes, symptoms, and initial symptom assessments including ways to cope with stress, anxiety, and depression through problem-solving methods and developing psychological capital could strengthen a person’s mental strength and adjust him or herself to live happily in the rapidly changing world.